P1025HISTOLOGICAL AND CLINICAL FINDINGS IN ADULT AUTOPSIES OF TYPE 2 DIABETES MELLITUS PATIENTS WITH OR WITHOUT DIABETIC KIDNEY DISEASE. (6th June 2020) - Gimenez-Civera, Elena; Puchades Montesa, Maria Jesãºs; Terrádez, Liria; Moscardo, Anais; D'Marco, Luis; Pérez Ys, Aurora; Moncho, Francesc; Perez-Bernat, Elisa; Panizo Gonzalez, Nayara; Tomas, Patricia; Gonzalez-Rico, Miguel; Gorriz, Jose Luis
Abstract: Background and Aims: Few studies have analyzed early lesions of diabetic nephropathy (DN) in those patients who do not have clinical signs of this involvement, since the indication of renal biopsy is usually performed in patients with significant renal manifestations.The aim of the study was to analyze renal histological lesions from autopsies of diabetic patients with or without clinical expression of DN. Thus, we analyze their correlation according to the presence or absence of proteinuria (albumin/creatinine to ratio > 300). Autopsies from non-diabetic patients was used as a control group. Method: Kidneys from autopsies of 21 patients with type 2 diabetes mellitus (T2DM) and 4 non-diabetic controls were analyzed by two pathologists. The histological lesions score of DN was performed according to the classification of Tervaert et al. (JASN. 2010; 21: 556–63), and a description of histological findings, clinical and analytical data were made. Results: The mean glomeruli per sample was: 170 ±88. Patient demographics of autopsies: mean age 76 ± 11 years, mean duration of diabetes 6.08 ± 3.2 years (20%> 10 years). Last known eGFR: 51 ± 28, HbA1c: 7.3 ± 1.9%. Albuminuria and cardiovascular disease were present in 42% and 60% of patients with T2DM. Histological and clinical data are shown in Table and Graphics . Conclusion: A high percentage of diabetics without early clinical lesions of DN (albuminuria) already express moderate to severe histological changes, especially severe mesangial expansion and severe glomerular vascular lesions. The control group showed minimal histological lesions except for mild expansion of the mesangium and inflammation associated with IFTA. Our data suggest renal involvement in T2DM is present in earlier stages (patients without albuminuria). Therefore, early metabolic control is important, as well as other risk factors that may influence in the development of DN. Large sample size studies are pending to confirm these data.